Application of dual-energy CT in assessing the efficacy of nasopharyngeal carcinoma and diagnosing metastatic lymph nodes - Wang, Yunnong; Dai, Feng; Li, Yang; Qiao, Wei; Li, Kang; Pan, Chunhan; Jiang, Qianlai; Fang, Shanyu; Kang, Zheng; Zhang, Xiuming (Frontiers in Oncology, 2025)
PurposeTo explore the value of dual-energy CT (DECT) in evaluating the efficacy of nasopharyngeal carcinoma (NPC) and in the detection of metastatic lymph nodes (MLNs).Materials and methodsFor this retrospective study, we collected and analyzed clinical and imaging data from 83 patients diagnosed with NPC via histopathology, who were admitted to the Radiotherapy Department from August 2022 to July 2024. The cohort consisted of 64 males and 19 females, with an average age of 50.86 ± 13.45 (years). All patients underwent DECT enhancement and MRI scanning before and after the first treatment course to assess the extent of lesions and lymph nodes (LNs). A total of 423 LN imaging datasets were analyzed. We measured iodine concentration (IC), effective atomic number (Zeff), electron density (ED), and normalized iodine concentration (NIC). Additionally, we recorded the magnetic resonance ADC values of the LNs.ResultsStatistical analysis of Zeff, ED, and NIC values of lesion and LNs revealed no significant differences between groups (p > 0.05). The Zeff, ED, and NIC values for lesions and LNs were significantly lower after treatment than before (p < 0.05). Receiver operating characteristic (ROC) analysis for MLNs indicated that the area under the ROC curve (AUC) for NIC indicated high accuracy.ConclusionDECT provides valuable functional parameters for assessing the efficacy of NPC and demonstrates significant clinical application value. Notably, the NIC parameter shows high diagnostic efficacy for MLNs, comparable to the ADC value obtained from MRI.